ENTREPRENEURIAL MINDSET SEBAGAI DETERMINAN KESIAPAN BERWIRAUSAHA MAHASISWA: SYSTEMATIC LITERATURE REVIEW - Habel Wilefri Al Hadad; Asmar Yulastri; Henny Yustisia; Yudha Aditya Fiandra (Jurnal Manajemen Pendidikan, 2026)
This study focuses on analyzing the role of entrepreneurial mindset as a key determinant in shaping students' entrepreneurial readiness. This study is based on the importance of comprehensively understanding the factors that influence students' entrepreneurial readiness. This study uses the Systematic Literature Review (SLR) method with the PRISMA approach through the analysis of 12 relevant scientific articles from 2016–2026. Data analysis was conducted using narrative synthesis and thematic analysis to identify patterns of relationships between variables that contribute to students' entrepreneurial readiness. The results show that entrepreneurial mindset plays a role in connecting psychological factors (self-efficacy, motivation, creativity, resilience), entrepreneurship education, entrepreneurial skills, and external factors such as the entrepreneurial ecosystem, social media, and role models. The findings also indicate that entrepreneurship education does not have a direct impact, but the formation of an entrepreneurial mindset and the support of a conducive environment will have a direct impact on students' entrepreneurial readiness. The novelty of this research lies in the development of an integrative synthesis model that positions entrepreneurial mindset as a key variable bridging all determinants of students' entrepreneurial readiness.